Viral Infections, the Microbiome, and Probiotics - Harper, Ashton; Vijayakumar, Vineetha; Ouwehand, Arthur C.; ter Haar, Jessica; Obis, David; Espadaler, Jordi; Binda, Sylvie; Desiraju, Shrilakshmi; Day, Richard (Frontiers in Cellular and Infection Microbiology, 2021)
Viral infections continue to cause considerable morbidity and mortality around the world. Recent rises in these infections are likely due to complex and multifactorial external drivers, including climate change, the increased mobility of people and goods and rapid demographic change to name but a few. In parallel with these external factors, we are gaining a better understanding of the internal factors associated with viral immunity. Increasingly the gastrointestinal (GI) microbiome has been shown to be a significant player in the host immune system, acting as a key regulator of immunity and host defense mechanisms. An increasing body of evidence indicates that disruption of the homeostasis between the GI microbiome and the host immune system can adversely impact viral immunity. This review aims to shed light on our understanding of how host-microbiota interactions shape the immune system, including early life factors, antibiotic exposure, immunosenescence, diet and inflammatory diseases. We also discuss the evidence base for how host commensal organisms and microbiome therapeutics can impact the prevention and/or treatment of viral infections, such as viral gastroenteritis, viral hepatitis, human immunodeficiency virus (HIV), human papilloma virus (HPV), viral upper respiratory tract infections (URTI), influenza and SARS CoV-2. The interplay between the gastrointestinal microbiome, invasive viruses and host physiology is complex and yet to be fully characterized, but increasingly the evidence shows that the microbiome can have an impact on viral disease outcomes. While the current evidence base is informative, further well designed human clinical trials will be needed to fully understand the array of immunological mechanisms underlying this intricate relationship.